Comparative Analysis of the Concept of Women's Leadership in Tafsir Al-Misbah and Tafsir An-Nur - Syahida, Zulfa Rahma; Romadlon , Arif Firdausi Nur; Edy Wirastho (Jurnal Semiotika Quran, 2025)
Women's leadership is an important and controversial issue in contemporary Muslim society, where interpretations of the Qur'an regarding the position of women as leaders still vary. Meanwhile, global data shows that there is still a significant gender gap in leadership positions. This study aims to compare and analyze the views of Tafsir Al-Misbah by M. Quraish Shihab and Tafsir An-Nur by Hasbi Ash-Shiddieqy on women's leadership based on relevant verses of the Qur'an,  particularly  QS. An-Nisa' [4]: 34  and QS. At-Taubah [9]: 71.  The method used is qualitative with a comparative analysis approach, which compares the two interpretations in depth. The results of the study show that both interpretations agree on placing men as leaders in the domestic sphere due to their responsibility for maintenance and protection, but still open up space for women to lead in the public sphere as long as they meet the requirements of trustworthiness and capability. The Tafsir Al-Misbah tends to be moderate, taking into account natural aspects, while the Tafsir An-Nur is more progressive and inclusive, emphasizing the principles of justice, deliberation, and gender equality. The contribution of this research is to enrich the discourse on contemporary interpretation and offer a distinctive Indonesian perspective in the global dialogue on women's leadership and gender justice in Islam.